Implementation of E-Government with the RESTFUL API Method on the Population Data Management System in Pasar Kemis District - Yulianjani, Arsi; April Yanto Wijaya, Gede Dito; Christopher, Anthonius (Journal Sensi: Strategic of Education in Information System, 2025)
Pasar Kemis currently uses a manual system for population data, leading to issues like slow data collection and difficulty searching. To improve efficiency, they propose a new web-based system built with PHP and CodeIgniter. This system will use Restful API for data exchange and be tested with Black Box Testing. Researchers gathered information through observation, interviews, and documents. UML will be used for system design, and prototyping with Adobe XD will help analyze advantages and disadvantages. The goal is to replace the traditional system with a computerized one for easier data entry, research, and report generation, ultimately benefitting the district government.